PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO INTERAKTIF TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPAS DI KELAS IV SD NEGERI 5 TONJA DENPASAR - Ni Kadek Mila Yeloni; I Made Wiguna Yasa; Ni Kadek Supadmini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
This study investigated the effect of the Project Based Learning(PjBL) model assisted by interactive video on the creativethinking skills of fourth-grade students at SD Negeri 5 Tonja. A quasi-experimental design with a non-equivalent control groupwas employed involving 64 students divided into experimentaland control classes. Data were collected through multiple-choice tests and project assessment rubrics and analyzed usingan independent sample t-test. The findings showed that theexperimental class achieved a higher mean posttest score(80.13) than the control class (67.38), with a significantdifference (p = 0.000). Therefore, PjBL assisted by interactivevideo effectively improved students’ creative thinking skills.